2010
DOI: 10.1111/j.1743-6109.2009.01664.x
|View full text |Cite
|
Sign up to set email alerts
|

Bicycle Riding and Erectile Dysfunction: A Review

Abstract: Introduction For many years, reports in the literature have implicated bicycle riding as causing increased risk of erectile dysfunction (ED). Perineal compression during cycling has been associated with the development of sexual complications. Aim To review current literature on the rationale for ED from bicycle riding and outcome of bicycle riding on erectile function and to present available research on preventative measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 47 publications
0
49
0
4
Order By: Relevance
“…Downward tilting of the saddle also decreases the anterior perineal stress but may lead to increased pressure on the hands and to instability on the seat, forcing the rider to continually move backward. 31,32 Concerning the role of a perineal hole, it has been shown that a central cut-out did not lessen perineal pressure but, on the contrary, could increase it. 16,[33][34][35] Sommer et al 32 attributes this to the fact that the positioning of the hole might not be well understood by manufacturers.…”
Section: Bicycle Characteristicsmentioning
confidence: 98%
“…Downward tilting of the saddle also decreases the anterior perineal stress but may lead to increased pressure on the hands and to instability on the seat, forcing the rider to continually move backward. 31,32 Concerning the role of a perineal hole, it has been shown that a central cut-out did not lessen perineal pressure but, on the contrary, could increase it. 16,[33][34][35] Sommer et al 32 attributes this to the fact that the positioning of the hole might not be well understood by manufacturers.…”
Section: Bicycle Characteristicsmentioning
confidence: 98%
“…Il delicato equilibrio fra strutture muscolari, vascolari e nervose viene alterato dalla pressione e dalle temperatura cui gli atleti espongono il perineo. Per quanto la ricerca sia finalizzata a produrre sellini più "performanti", per gli atleti di entrambi i sessi esiste il concreto rischio di andare incontro a disfunzioni sessuali su base traumatica [14,15].…”
Section: Effetti Dell'attività Sportiva Sull'attività Sessualeunclassified
“…This concept has been supported by the association between bicycling and ED. This relationship was first noted in a number of case reports, but later cross-sectional studies found that young men who bicycle more than 3 hours a week have an increased risk of developing ED [7]. Bicycling has been shown to reduce the peak cavernosal artery systolic velocity to 0 due to perineal pressure from bicycle seats, and is thought to temporarily occlude penile vessels and lead to focal arterial occlusive disease [7].…”
Section: Etiology Of Erectile Dysfunctionmentioning
confidence: 99%